Biodiesel production from rice hulls using fast pyrolysis a plant design - Gacuan, Jake M.; Sangalang, Hannah Carize M.; Vicher, Victorio L.; Agutaya, Jonas Karl Christopher N. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The purpose of this plant design is to utilize biomass for biodiesel production. Since the Philippines is an agricultural country, the supply of biomass is abundant specifically the supply of rice hulls. The main conversion process is fast pyrolysis, which is the burning of rice hulls at a high temperature and a very short residence time. After obtaining the pyrolysis oil, it is refined via hydrotreating and distillation. The potential market for biodiesel in the Philippines is huge because of the Biofuels Act that mandates the use of biodiesel in the transport sector. By year 2015, the current biodiesel industry will no longer be able to support the growing demand for biodiesel and thus, additional sources for biodiesel must be considered. The proposed plant will be built in San Leonardo, Nueva Ecija which is the province with the highest production of rice in the country. It will have a feed of 160,000 metric tons of rice hulls per year, and an annual yield of 20.63 million liters per year of biodiesel and 11.20 million liters per year of gasoline.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Rice hulls as fuel; Biodiesel fuels